Dynamics of Solidarity and Resistance: Local Community Responses to Rohingya Refugees in Aceh - Nurul Fajri; Novi Susilawati; Azharul Husna (LPPM Universitas 17 Agustus 1945 Semarang, 2026)
The arrival of Rohingya refugees in Aceh has generated complex social responses among local communities, characterized by the coexistence of solidarity and resistance. This study examines how local communities negotiate humanitarian values, cultural norms, and structural pressures in responding to the presence of refugees. Using a qualitative approach, the research applies the analytical framework of Miles and Huberman, integrating social capital theory and human needs theory to interpret community responses. Data were collected through in-depth interviews, field observations, and analysis of media reports. The findings indicate that solidarity initially emerged strongly, rooted in religious values and local cultural norms emphasizing humanitarian assistance. However, over time, resistance developed due to economic concerns, perceived inequality in aid distribution, and socio-cultural tensions. Rather than replacing solidarity, resistance coexisted with it, creating an ambivalent social dynamic within host communities. This study argues that local responses to forced migration should not be understood in binary terms of acceptance or rejection, but as a dynamic process shaped by moral commitments and structural constraints. The research contributes to sociological discussions on forced migration and community relations by highlighting how solidarity and resistance operate simultaneously within local contexts.